GLO GERM AND COVID-19: ILLUMINATING HYGIENE AND PROMOTING TRANSMISSION AWARENESS - ZATLA, Ilyes; BOUBLENZA, Lamia; LEMERINI, Wafaa; TRIQUI , Chahinez (African Journal of Infectious Diseases (AJID), 2024)
Background: Maintaining effective surface hygiene and preventing contamination is of paramount importance. Our study introduces Glo Germ, a versatile product available in various forms, which possesses the unique ability to reveal hidden truths under ultraviolet light, enhance understanding of hygiene, and spread awareness of COVID-19 transmission and preventive measures. Materials and Methods: A comprehensive study was conducted to assess different surface cleaning techniques’ effectiveness. Glo Germ, containing a fluorescent dye activated by ultraviolet light, was used to visualize germ spread and compare disinfectant cleaners’ efficacy. The study encompassed diverse surfaces and materials, aiming to identify optimal cleaning techniques for each context. Furthermore, a small illustrative study was conducted during a COVID-19 awareness presentation involving students. Glo Germ was applied to hands, revealing its subsequent spread to faces and surfaces. This visual experiment effectively emphasized hand hygiene and mask-wearing importance. Results: Results indicated that while water alone achieved satisfactory cleaning results, using detergent and the appropriate cleaning tools further improved efficacy. Notably, adhering to consistent patterns and applying pressure during cleaning proved essential. The student demonstration showed how contaminants spread quickly, highlighting hand hygiene’s significance and the potential extent of contamination through sneezing. Conclusion: Glo Germ inclusion in these experiments highlights its potential in educating about surface cleaning and microbial transmission, offering an interactive and engaging approach to promoting personal hygiene and fostering illness prevention awareness.